Paper-based microfluidic aluminum-air batteries: Toward next-generation miniaturized power supply - Shen, Liu Liu; Zhang, Gui Rong; Biesalski, Markus; Etzold, Bastian J.M. (Lab on A Chip, 2019)
Paper-based microfluidics (lab on paper) emerges as an innovative platform for building small-scale devices for sensing, diagnosis, and energy storage/conversions due to the power-free fluidic transport capability of paper via capillary action. Herein, we report for the first time that paper-based microfluidic concept can be employed to fabricate high-performing aluminum-air batteries, which entails the use of a thin sheet of fibrous capillary paper sandwiched between an aluminum foil anode and a catalyst coated graphite foil cathode without using any costly air electrode or external pump device for fluid transport. The unique microfluidic configuration can help overcome the major drawbacks of conventional aluminum-air batteries including battery self-discharge, product-induced electrode passivation, and expensive and complex air electrodes which have long been considered as grand obstacles to aluminum-air batteries penetrating the market. The paper-based microfluidic aluminum-air batteries are not only miniaturized in size, easy to fabricate and cost-effective, but they are also capable of high electrochemical performance. With a specific capacity of 2750 A h kg-1 (@20 mA cm-2) and an energy density of 2900 W h kg-1, they are 8.3 and 12.6 times higher than those of the non-fluidic counterpart and significantly outperform many other miniaturized energy sources, respectively. The superior performance of microfluidic aluminum-air batteries originates from the remarkable efficiency of paper capillarity in transporting electrolyte along with O2 to electrodes.
CRIS-Team Scopus Importer:2023-08-15